2014
DOI: 10.1089/scd.2014.0070
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Pathway Activation in Normal and Hyperglycemic Rats Differs in the Stem Cells of Visceral and Subcutaneous Adipose Tissue

Abstract: The precise mechanisms underlying the differential function and cardiometabolic risk of white adipose tissue (WAT) remain unclear. Visceral adipose tissue (V WAT ) and subcutaneous adipose tissue (SC WAT ) have different metabolic functions that seem to be ascribed to their different intrinsic expansion capacities. Here we have hypothesized that the WAT characteristics are determined by the resident adipose-derived stem cells (ASCs) found in the different WAT depots. Therefore, our objective has been to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…Another identified candidate was claudin 1 ( CLDN1 ) encoding an integral membrane protein and a component of tight junction strands. We further observed the heart and neural crest derivatives expressed 2 ( HAND2 ) which may play a role in adipogenic differentiation via NOTCH signaling [30], [31] and the cluster of differentiation 36 ( CD36 ), which is involved in lipid metabolism [32], [33]. Further, we also confirmed known candidate genes such as the homeobox C6 ( HOXC6 ) and the peroxisome proliferator-activated receptor gamma ( PPARG ).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Another identified candidate was claudin 1 ( CLDN1 ) encoding an integral membrane protein and a component of tight junction strands. We further observed the heart and neural crest derivatives expressed 2 ( HAND2 ) which may play a role in adipogenic differentiation via NOTCH signaling [30], [31] and the cluster of differentiation 36 ( CD36 ), which is involved in lipid metabolism [32], [33]. Further, we also confirmed known candidate genes such as the homeobox C6 ( HOXC6 ) and the peroxisome proliferator-activated receptor gamma ( PPARG ).…”
Section: Resultssupporting
confidence: 57%
“…Hand2 is involved in Notch signaling in heart development of mice [41]. Considering that NOTCH signaling also plays a major role in adipogenic differentiation [30], [31], mainly through inhibiting ASC (Adipose tissue-Derived-Stem Cells) differentiation to adipocytes and thereby affecting the adipose tissue expansion capacity [30], this might indicate reduced adipocyte differentiation in OVAT. In line with this, increased Notch signaling in mice blocked the expansion of white adipose tissue, ectopic fat accumulation and insulin resistance [42], which further supports the potential dysfunctional role of OVAT [1], [2].…”
Section: Discussionmentioning
confidence: 99%
“…The reservoir of stem cells in subcutaneous adipose tissue is known to change in diabetes. Adipose‐derived stem cells (ASCs), derived from the stromal vascular fraction, exhibit impaired viability, and differentiation (Ferrer‐Lorente et al, ,), including endothelial cell (EC), and angiogenic differentiation potential (Koci et al, ; Policha et al, ; Rennert et al, ). Diabetes is also known to limit the therapeutic potential of endothelial progenitor cells (EPCs) and bone marrow‐derived progenitor cells (BMPCs) (Tepper et al, ; Fadini et al, ; Li et al, ), and has been proposed to have deleterious effects on stem cells due to oxidative stress (Saki et al, ).…”
mentioning
confidence: 99%
“…Multiple signaling pathways, several of which are involved in stem cell maintenance, are affected by diabetes in adipose tissue, including the Notch, Wnt, fibroblast growth factors (FGF) (Ferrer‐Lorente et al, ,), and the bone morphogenetic proteins (BMPs) (Dunn, ; Qian et al, ). The BMPs are important for both adipose tissue development and vascular formation (Schulz and Tseng, ; Tang and Lane, ; Dyer et al, ), and recent studies suggest that BMP expression is altered in response to diabetes in multiple tissues.…”
mentioning
confidence: 99%
“…Similarly, Griesche et al () demonstrated that, while incorporating additional wash steps and immunoselection for several markers into the isolation protocol improved the homogeneity of ASC cultures, these steps also resulted in considerably lower cell yields, and had little impact on the differentiation potential of these cells. Moreover, expression of CD29, CD90, and CD105 may vary between ASCs from different adipose tissue depots (Ferrer‐Lorente, Bejar, & Badimon, ), or with obesity, high‐fat feeding, and exercise (Oñate et al, ; Pincu et al, ), and therefore immunoselection for these markers may differentially affect cell yields in studies where these factors are being examined.…”
Section: Primary Ascsmentioning
confidence: 99%